Educational Jobs: Youth and Employability in the Social Economy Investigations in Italy, Malta, Portugal, Romania, Spain, United Kingdom - Boffo, Vanna (Studies on Adult Learning and Education, 2015)
In Europe the social economy employs almost 15 million workers. During the crisis years, unlike other sectors, it has often generated an increase in jobs. The aim of this comparative study is to investigate how to allow the supply and demand for young people to meet in the different types of social economy bodies. In particular, it concentrates on the problem of how to bring into line initial university training and the skills required by these organizations. The focus is placed on the varied family of training workers present in at least 75% of the organizations, whose professionalism is nevertheless rarely acknowledged. The papers proposed in this book try to identify the most suitable solutions at the level of curriculum, career development and accompanying measures, while drawing solutions from objective findings and not from training system needs or convictions.